Isolated Renal Metastasis from Non-Small-Cell Lung Cancer: Report of 2 Cases - Masaki Tomita; Takanori Ayabe; Eiichi Chosa; Kunihide Nakamura (Case Reports in Surgery)
Renal metastasis from non-small-cell lung cancer is rather uncommon; isolated metastasis especially is rare. Herein we report 2 cases who developed a solitary renal metastasis after undergoing a curative resection for non-small-cell lung cancer. They received nephrectomy.